2000
DOI: 10.1002/(sici)1098-2264(200006)28:2<153::aid-gcc4>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

A consistent pattern ofRIN1 rearrangements in oral squamous cell carcinoma cell lines supports a breakage-fusion-bridge cycle model for 11q13 amplification

Abstract: Gene amplification is a common feature of tumors. Overexpression of some amplified genes plays a role in tumor progression. Gene amplification can occur either extrachromosomally as double‐minute chromosomes (dmin) or intrachromosomally in the form of homogeneously staining regions (hsrs). Approximately one‐half of our oral squamous cell carcinomas (OSCCs) are characterized by amplification of band 11q13, usually as an hsr located entopically (occurring or situated at the normal chromosomal site, as opposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Our findings also suggest the presence of two or more as-yet-unidentified breakage hotspots or fragile sites that may be responsible for the breakpoints defining the 11q13 amplicon core. The observation of consistent breakpoints also supports our previous hypothesis that 11q13 amplification arises as a result of BFB cycles in OSCC (30).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings also suggest the presence of two or more as-yet-unidentified breakage hotspots or fragile sites that may be responsible for the breakpoints defining the 11q13 amplicon core. The observation of consistent breakpoints also supports our previous hypothesis that 11q13 amplification arises as a result of BFB cycles in OSCC (30).…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that the fragile sites form boundaries of genomic amplifications (Coquelle et al, 1997;Shuster et al, 2000). A breakage-fusion-bridge mechanism of amplification at 11q13 possibly involves breaks at proximal 11q13 (FRA11A) and at INT2 (FRA11H) (Shuster et al, 2000). We speculate therefore that the allelic imbalance at the INT2 locus in some of the primary tumors was preceded by a deletion at D11S913.…”
Section: Discussionmentioning
confidence: 78%
“…Amplification of this genomic region is observed in a number of human tumors (Shuster et al, 2000). It has been suggested that the fragile sites form boundaries of genomic amplifications (Coquelle et al, 1997;Shuster et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CEP11 probe labeled with SpectrumGreen s from Vysis was used for enumerating the chromosome 11 centromere. The labeled BAC clone and CEP11 were then used as probes for FISH using standard procedures described previously (Shuster et al, 2000;Reshmi et al, 2004). Approximately 200 interphase nuclei were analysed for each sample.…”
Section: Cell Culturementioning
confidence: 99%